Anti-Inflammatory Properties of Statin-Loaded Biodegradable Lecithin/Chitosan Nanoparticles: A Step Toward Nose-to-Brain Treatment of Neurodegenerative Diseases - Clementino, Adryana Rocha; Marchi, Cinzia; Pozzoli, Michele; Bernini, Franco; Zimetti, Francesca; Sonvico, Fabio (Frontiers in Pharmacology, 2021)
Nasal delivery has been indicated as one of the most interesting alternative routes for the brain delivery of neuroprotective drugs. Nanocarriers have emerged as a promising strategy for the delivery of neurotherapeutics across the nasal epithelia. In this work, hybrid lecithin/chitosan nanoparticles (LCNs) were proposed as a drug delivery platform for the nasal administration of simvastatin (SVT) for the treatment of neuroinflammatory diseases. The impact of SVT nanoencapsulation on its transport across the nasal epithelium was investigated, as well as the efficacy of SVT-LCNs in suppressing cytokines release in a cellular model of neuroinflammation. Drug release studies were performed in simulated nasal fluids to investigate SVT release from the nanoparticles under conditions mimicking the physiological environment present in the nasal cavity. It was observed that interaction of nanoparticles with a simulated nasal mucus decreased nanoparticle drug release and/or slowed drug diffusion. On the other hand, it was demonstrated that two antibacterial enzymes commonly present in the nasal secretions, lysozyme and phospholipase A2, promoted drug release from the nanocarrier. Indeed, an enzyme-triggered drug release was observed even in the presence of mucus, with a 5-fold increase in drug release from LCNs. Moreover, chitosan-coated nanoparticles enhanced SVT permeation across a human cell model of the nasal epithelium (×11). The nanoformulation pharmacological activity was assessed using an accepted model of microglia, obtained by activating the human macrophage cell line THP-1 with the Escherichia coli–derived lipopolysaccharide (LPS) as the pro-inflammatory stimulus. SVT-LCNs were demonstrated to suppress the pro-inflammatory signaling more efficiently than the simple drug solution (−75% for IL-6 and −27% for TNF-α vs. −47% and −15% at 10 µM concentration for SVT-LCNs and SVT solution, respectively). Moreover, neither cellular toxicity nor pro-inflammatory responses were evidenced for the treatment with the blank nanoparticles even after 36 h of incubation, indicating a good biocompatibility of the nanomedicine components in vitro. Due to their biocompatibility and ability to promote drug release and absorption at the biointerface, hybrid LCNs appear to be an ideal carrier for achieving nose-to-brain delivery of poorly water-soluble drugs such as SVT.